2017
DOI: 10.1111/nmo.13212
|View full text |Cite
|
Sign up to set email alerts
|

Xenotransplantation of human intestine into mouse abdomen or subcutaneous tissue: Novel platforms for the study of the human enteric nervous system

Abstract: Abdominal xenografts represent a novel model that supports the growth and development of fetal human intestine. This in vivo approach will be a useful method to study maturation of the ENS, the pathophysiology of neurointestinal diseases, and the long-term survival and functional differentiation of neuronal stem cells for the treatment of enteric neuropathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
0
12
1
Order By: Relevance
“…While ectopic and not functional, these gut implants develop characteristic structures of the human gut with extensive vasculature and their structural features are highly similar to those of normal human gut, including mucosal villous epithelium, crypt structures, blood vessels and enteric nervous system. We and others have previously shown that virtually all the cell types that are present in the normal human gut are also present in these xenografts (Savidge et al, 1995;Savidge et al, 2001;Golan et al, 2009;Golan et al, 2011;Nissim-Eliraz et al, 2017;Nagy et al, 2018;Bruckner et al, 2019). Moreover, the general architecture of the gut appears normal, and the tissue is well-vascularized by a human capillary system that anastomoses to the circulatory system of the murine host.…”
Section: Ibdmentioning
confidence: 89%
See 2 more Smart Citations
“…While ectopic and not functional, these gut implants develop characteristic structures of the human gut with extensive vasculature and their structural features are highly similar to those of normal human gut, including mucosal villous epithelium, crypt structures, blood vessels and enteric nervous system. We and others have previously shown that virtually all the cell types that are present in the normal human gut are also present in these xenografts (Savidge et al, 1995;Savidge et al, 2001;Golan et al, 2009;Golan et al, 2011;Nissim-Eliraz et al, 2017;Nagy et al, 2018;Bruckner et al, 2019). Moreover, the general architecture of the gut appears normal, and the tissue is well-vascularized by a human capillary system that anastomoses to the circulatory system of the murine host.…”
Section: Ibdmentioning
confidence: 89%
“…We have examined the activation of NF-B in segments of human fetal gut transplanted and developing in a subcutaneous, sterile environment in SCID mice. The experimental model system we have used was first reported by Winter et al in 1991(Winter et al, 1991 and refined in our laboratories for study of the human enteric nervous system (Nagy et al, 2018), human-specific pathogens (Golan et al, 2009;Golan et al, 2011) and inflammatory bowel diseases (IBD) (Canavan et al, 2016;Bruckner et al, 2019;Goldberg et al, 2019). Fetal gut was obtained after informed consent from pregnancy terminations performed legally at 12-18 weeks gestational age and transplanted subcutaneously in mature SCID mice.…”
Section: Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that there is some heterogeneity between different donors; for example, age, sex, body mass index, and site of harvest are known to have an effect on the properties of the ASCs [43][44][45][46][47]. Xenotransplantation has been used before to study development, physiology, and pathophysiology of human tissues in animal models, for example, enteric nervous system [48] and rodent models have been tested in treatment of stroke [49] and myocardial infarct [50]. However, there are differences in human and animal physiology that have to be kept in mind when interpreting the results [51].…”
Section: Discussionmentioning
confidence: 99%
“…While responses are simulated by tumor engraftment, alloresponses are simulated by engraftment of human cells or tissues; the most common models being those that engraft human skin, 86 islets of Langerhans, 87 or blood vessels. 88 The most widely used model is that of human skin allotransplantation. 89 - 93 Skin grafts benefit from tissue accessibility permitting continuous visible monitoring and from an established progression of rejection in skin architecture and leukocyte infiltration.…”
Section: Micementioning
confidence: 99%